THE LEXICOGRAMMATICAL APPROACH: ENHANCING DELIVERY SKILLS THROUGH COMMUNICATIVE GRAMMAR DEVELOPMENT - Suseno, Edy (JETA (Journal of English Teaching and Applied Linguistic), 2024)
It's critical to use a language in daily interactions. It is the method by which people communicate ideas. Many EFL students struggle to use the language they learn for communication. In order to achieve this goal, A few theories were offered to assist in correcting such a defect. The main phase is devoted to expanding one's vocabulary. It is the material that will be utilized to put the ideas into words. Grammar rules are used in order to give it meaning. That's the way sentences are put together. When grammar rules and vocabulary are used to construct sentences, the delivery gains significance. It is an advantage of employing lexico grammar in spoken communication. Nonetheless, it's necessary to learn how to understand idioms. Using the lexicogrammar approach to analyze it aids in the pupils' grammatical recognition. The conclusions are the result of a qualitative investigation of the theories. It has been discovered that learning speaking via lexicogrammar and communicative grammar techniques improves the fluency and understanding of the speech. Applying it to the teaching of related subjects aids teachers. It also prompts more in-depth observation from other researchers.